2012
DOI: 10.1523/jneurosci.4031-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Linking Pain and the Body: Neural Correlates of Visually Induced Analgesia

Abstract: The visual context of seeing the body can reduce the experience of acute pain, producing a multisensory analgesia. Here we investigated the neural correlates of this "visually induced analgesia" using fMRI. We induced acute pain with an infrared laser while human participants looked either at their stimulated right hand or at another object. Behavioral results confirmed the expected analgesic effect of seeing the body, while fMRI results revealed an associated reduction of laser-induced activity in ipsilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
139
8
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 56 publications
11
139
8
1
Order By: Relevance
“…However whereas these pain thresholds data have recently been extended with explicit ratings of pain experience [22], we did not observe similar effects in explicit pain ratings in experiment 1 and 2. Consistently with our results, a recent study (conducted in two different laboratories) showed that explicit pain ratings for stimuli delivered to the biological hand did not change during the RHI [54].…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…However whereas these pain thresholds data have recently been extended with explicit ratings of pain experience [22], we did not observe similar effects in explicit pain ratings in experiment 1 and 2. Consistently with our results, a recent study (conducted in two different laboratories) showed that explicit pain ratings for stimuli delivered to the biological hand did not change during the RHI [54].…”
Section: Discussioncontrasting
confidence: 94%
“…We hypothesized that the increased self-identification, when seeing the virtual body stroked in a congruent fashion, would be reflected in changes in the processing of painful stimuli akin to those described during the direct observation of one's own body typically consisting of a reduced response to painful stimuli [22,20,44]. Questionnaire data showed that higher selfidentification was recorded with the avatar only when presented with an anatomically correct body configuration and when stroked congruently, according to the literature [4,53,28,9,8].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations